A 13‐week toxicity study of acrylamide administered in drinking water to hamsters. Issue 1 (6th November 2012) - Imai, Toshio; Kitahashi, Tsukasa
ABSTRACT: Acrylamide (AA) is known to induce tumors in various organs/tissues in rats and mice. Epidemiological studies of oral exposure have generated controversial results but mortality studies of people who work with AA have indicated increased rates of pancreatic cancer. In the present study, for dose selection for chronic toxicity/carcinogenicity studies, 13‐week toxicity of AA was evaluated in Syrian hamsters, which are sensitive to induction of pancreatic ductal carcinogenesis, at concentrations required to provide doses of 0 (control), 20, 30 and 50 mg kg –1 body weight in drinking water. Treatment with AA caused abnormal gait advancing to hind limb paralysis in all males and females at 50 mg kg –1 . Body weights in 30 and 50 mg kg –1 males and 50 mg kg –1 females were lower than in the controls. At termination of the study, red blood cells (RBC) and hemoglobin (Hb) were decreased or showed a tendency for a decrease at 20 and 30 mg kg –1 in females. Microscopically, axonal/myelin degeneration of sciatic nerves was observed in all AA‐treated groups with dose dependence. No obvious changes were found in pancreatic ducts/ductules in any groups of animal. These results indicated the maximum tolerated dose for long‐term studies of AA to be 20 mg kg –1 or less in both male and female Syrian hamsters. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Thirteen‐week toxicity of (AA) was evaluated in Syrian hamsters, at concentrations of 0 (control), 20, 30 and 50 mg kg –1 body weight in drinking water. Treatment with AA caused peripheral nerve disorders in all AA‐treated groups with dose dependence. In addition, testicular toxicity at 50 mg kg –1 and lowered body weights at 30 and 50 mg kg –1 were observed. These results indicated the maximum tolerated dose for long‐term studies of AA to be 20 mg kg –1 or less in Syrian hamsters.